(untitled) (LEARNing Landscapes, 2014)
What teachers learn about classroom management in education classes often results in behaviour strategies that do not account for the individuality of each student. Teachers would benefit greatly from a common formula for effective problem solving and decision making with regard to choosing when to use the strategies in their "tool box." The solution proposed is the building of an individual biopsychosocial, multimodal profile for each student with chronic challenging behaviours.